O014 Oxidised zirconium versus cobalt-chrome femoral heads in total hip arthroplasty: a multi-centre prospective double-blinded randomised controlled trial with 10-years follow-up. (22nd July 2022) - Kayani, B; Baawa, J; Fontalis, A; Tahmassebi, J; Wardle, N; Middleton, R; Hutchinson, J; Haddad, FS
Abstract: Introduction: This study reports the ten-year polyethylene liner wear rates, incidence of osteolysis, clinical outcomes and complications of a three-arm, multicentre randomised controlled trial comparing Cobalt-Chrome (CoCr) and Oxidised Zirconium (OxZr) femoral heads with ultra-high molecular weight polyethylene (UHMWPE) versus highly cross-linked polyethylene(XLPE) liners in total hip arthroplasty (THA). Methods: Patients undergoing THA from four institutions were prospectively randomised into three groups. Group A received a CoCrfemoral head and XLPE liner; Group B received an OxZrfemoral head and XLPE liner; and Group C received an OxZr femoral head and UHMWPE liner. Patients and observers recording study outcomes were blinded to the treatment groups at each follow-up interval. The outcomes of 262 study patients were analysed at ten years follow-up after THA. Results: At ten years follow-up, increased linear wear rates were recorded in group C compared to group A (0.133 ± 0.21 mm/yr vs 0.031 ± 0.07 mm/yr respectively, p<0.001) and group B (0.133 ± 0.21 mm/yr vs 0.022 ± 0.05 mm/yr respectively, p<0.001). Patients in group C were associated with increased risk of osteolysis and aseptic loosening requiring revision surgery compared with group A (7/133 vs 0/133 respectively, p=0.007) and group B (7/133 vs 0/135 respectively, p=0.007). Conclusion: The use of UHMWPE was associated with progressively increased annual liner wear rates after THA. At ten years follow-up, this translated to UHMWPE leading to an increased incidence of osteolysis and aseptic loosening requiring revision THA, compared with XLPE. Take-home message: THA using XLPE liners is associated with improved long-term implant survivorship and reduced revision surgery compared with UHMWPE liners at long-term follow-up.